Karakteristik Beberapa Sifat Fisik, Kimia, dan Biologi Tanah Pada Sistem Pertanian Organik - Rizky Dharmawan Margolang, Rizky Dharmawan Margolang; Jamila Jamilah; Mariani Sembiring (Jurnal Agroekoteknologi, 2015)
The purpose of the study to determine the characteristis of some of the physical, chemical, and biological properties of soil in organic farming systems. The study was held about 6 month from November 2013 to April 2014 in Bioenvironment Education Center of Organic Farming Bahorok in Timbang Lawan village, Bahorok, at Langkat district for observe the characteristic of some physical, chemical, and biological characteristic of soil in organic farming system. This research was conducted with survey method by evaluation the soil character in the area of farming base on the time of application of the organic farming, so it taken 3 samples which are the organic farming system beginning from year 2005; the organic farming system beginning from year 2010; and farming system which not applicate the system of organic farming yet as the comparation and was conducted about 3 sample points. The result of this research showed that the application of organic farming can fix the physical and biological characteristic, but not chemistry charactreristic yet. The charactreristic of physical of the soil that can be fixed by the application of organic farming were changed soil color become darken, decreased bulk density of soil, increased the total soil pore space, and increased soil permeability from criteria a bit slow to medium. Whether for the infiltration of soil can not be increased yet with the organic farming application. The application of this organic farming system can not fix the chemical characteristic of soil as pH of soil, C-organic of soil, N-total of soil, and P-available still have the same criteria with conventional farming application, but for parameter K-exchange can increase this parameter from low to medium. The organic farming application can fix the biology characteristic by increase the soil respiration, number of soil microorganism and earthworms population.Keywords : organic farming, conventional farming, soil characteristic